Cherry Shrimp Neocaridina davidi (Bouvier 1904) (Crustacea: Decopoda: Atyidae) - Carrie Suen; Jennifer Lynn Gillett-Kaufman (EDIS, 2021)
Neocaridina davidi is a species of freshwater ornamental shrimp that belongs to the Atyidae family. Neocaridina davidi originates from Taiwan, but their popularity in the aquarium trade has led to them being available in other countries. This shrimp has different common names based on its color. Wild type shrimp are generally transparent or brown in color, however, generations of selective breeding have produced a variety of colors and patterns.